Implikasi Hukum Pidana Pers dalam Kasus Pengiriman Kepala Babi Ke Redaksi Tempo: Analisis Terhadap Kebebasan Pers dan Batasan Ekspresi - Salma Najla Amir; Dewina Mutiara Sholihat; Neyla Rida Shakira; Taun Taun (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Press criminal law has significant implications in the case of sending a pig's head to the editorial office of Tempo, an event that has drawn attention regarding press freedom and the limits of expression. This research aims to analyze how the provisions of press criminal law can be applied in the context of acts of intimidation against the media as occurred in this case. Employing a normative juridical study method with a case approach, this research will examine potential criminal violations and the relevance of the Press Law in providing protection for press freedom. The main focus of the analysis is to understand the limitations that can be imposed on expression, especially when such actions have the potential to threaten or create fear among journalists. This case is important to evaluate in order to maintain the dignity of the press as a free and independent pillar of democracy. Furthermore, this research is expected to contribute to a deeper understanding of how the legal system responds to actions that can undermine press freedom in Indonesia, as well as provide recommendations for more effective law enforcement in protecting press freedom without neglecting the principles of justice.